(3OGNd GdSj Gj Gjg (B:s (3GdeNGHQGJ GdeQcRjI GdCeQjcjI (B/s - (3cjSdQ, QhfGdOs; (3eGdc aGVds ((3YeGf (B:s (3GdCgdjI ddfTQ h GdJhRjY ,s, 1995)
(3aj gPG GdcJGH HYVG ef GSQGQ hcGdI GdeNGHQGJ GdeQcRjI GdJSSjI efgG h GdYedjI h GdJMdjdjI h efgG JJcTa ef fGMjI Ghdi Gf GdhdGjGJ GdeJMOI HUaJgG SjO GdYGde ceG JQi faSgG dG JQZH Gf Gf jJHhC GdMce TNU MJi h Gf GNJGQg TYHg aj GfJNGHGJ OjehbQGWjI (B.(3ceG JSJOd ef fGMjI GNQi Gf GdhdGjGJ GdeJMOI bO bWYJ ThWG WhjdG aj eLGd GdJbfjI h GdYdhe QHeG efMgG GdMb Gf Jbhd GffjGdGaVd aGf cGf dce Gf JMOhG ef SdWJj adJGJhG HeGGJjJs
Keywords: (3GdhdGjGJ GdeJMOI s; (3hcGdGJ GdeNGHQGJ GdeQcRjI s